Translation and psychometric evaluation of the Persian version of “good death inventory- short Form” from the perspective of family-members of cancer patients - Hosein Mohammadi Roshan; Abbas Ebadi; Leila Karimi; Salman Barasteh (BMC Psychology, 2023)
Abstract Introduction Achieving good death is among the objectives of palliative care in patients with cancer. There should be an instrument for evaluating the quality of palliative care provided by family members at the end of life. This study was done to assess the psychometric properties of good death inventory- short form according to the perspective of family of patients with cancer. Method This methodological study was done in 2022 at two hospitals in Tehran. The translation was done via forward-backward method. Face validity was examined through cognitive interviewing with 10 family members. The content validation, were used by assessment the opinions of 10 palliative care specialists. The construct validity was explored through exploratory factor analysis and examination of convergent validation with care evaluation scale 2.0, as well as inspection of correlation by answering two general questions of satisfaction with treatment and end of life quality of life. The scale’s reliability, internal consistency was calculated using Cronbach’s alpha coefficient and stability via test-retest. Results Overall, 204 family members of patients with cancer were included. In the exploratory factor analysis, three factors of peace, hope, and value as well as quality of care were extracted with cumulative variance of 41.8%.A significant and suitable correlation between the total scores of the participants Good death inventory-short form and care evaluation scale2.0 (r = 0.459, P < 0.001) and general satisfaction with end-of-life care (r = 0.423, p < 0.001) as well as the patient’s general quality of life (r = 0.539, p < 0.001). The Cronbach’s alpha coefficient for the questionnaire was found 0.842, and the stability was confirmed with Intra cluster correlation coefficient = 0.851. Conclusion the Persian version of good death inventory-short form is a valid and reliable questionnaire which can investigate the factors associated with good death according to patients’ family members’ perspective.